Environmental Conditions of the Berettyóújfalu Sub-Region - Tikász, Edit Ildikó (Acta Agraria Debreceniensis, 2005)
The purpose of this paper is to introduce the environmental conditions of the Berettyóújfalu sub-region, which is geographically located in Hajdú-Bihar County. I specifically target the regions’ relief, soil and hydrogeological conditions, climate, flora and fauna, natural value and present nature conservation activities. On the basis of my investigation of these points, I can state that although this sub-region has unfavorable soil conditions, polluted surface and subsurface waters, it is rich in thermal waters, nature reservations and wildlife. It’s disadvantageous characteristics can or should be amended, while the advantageous ones should be utilized by considering the principles of sustainability. At the end of this paper, I will make recommendations in connection with the latter point.